Attitudes toward water resilience and potential for improvement - Julia Baird; Gillian Dale; Gary Pickering (Global Sustainability)
Abstract Non-technical summary There is a global water crisis, brought on by human actions. The ways we make decisions about water must transform to solve it. We focused on the attitudes that people in society hold toward water to understand how close or far away we are from a broadly accepted worldview that supports this transformation (what we call ‘water resilience’). We found that, across six countries in the Global South and North, attitudes showed moderate support for water resilience. Many people also showed potential to increase their support.